Decade-long trends in surgery for acute Type A aortic dissection in England: A retrospective cohort study - Umberto Benedetto; Shubhra Sinha; Arnaldo Dimagli; Graham Cooper; Giovanni Mariscalco; Rakesh Uppal; Narain Moorjani; George Krasopoulos; Amit Kaura; Mark Field; Uday Trivedi; Simon Kendall; et al. (Elsevier, 2021)
Background: Little is known about variations in care and outcomes of patients undergoing surgical repair for type A aortic dissection(TAAD). We aim to investigate decade-long trends in TAAD surgical repair in England. Methods: Retrospective review of the National Adult Cardiac Surgery Audit, which prospectively collects demographic and peri‑operative information for all major adult cardiac surgery procedures performed in the UK. We identified patients undergoing surgery for TAAD from January 2009-December 2018, reviewed trends in operative frequency, patient demographics, and mortality. Findings: Over the 10-year period,3,680 TAAD patients underwent surgical repair in England. A doubling in the overall number of operations conducted in England was observed (235 cases in 2009 to 510 in 2018). Number of procedures per hospital per year also doubled(9 in 2009 to 23 in 2018). Overall, in-hospital mortality was 17.4% with a trend toward lower mortality in recent years(23% in 2009 to 14.7% in 2018). There was a significant variation in operative mortality between hospitals and surgeons. We also found that most patients presented towards the middle of the week and during winter. Interpretation: Surgery is the only treatment for acute TAAD but is associated with high mortality. Prompt diagnosis and referral to a specialist center is paramount. The number of operations conducted in England has doubled in 10 years and the associated survival has improved. Variations exist in service provision with a trend towards better survival in high volume centers. Funding: British Heart Foundation and NIHR Biomedical Research center(University Hospitals Bristol and Weston NHS Foundation Trust and University of Bristol).